The Curious Case of Carles Puigdemont-The European Arrest Warrant as an Inadequate Means with Regard to Political Offenses - König, Julia; Meichelbeck, Paulina; Puchta, Miriam (German Law Journal, 2021)
In contrast to traditional extradition law, the political offense exemption has been abolished within the framework of the European Arrest Warrant (EAW). Notwithstanding its overall success, the EAW does not constitute an adequate instrument with regard to political offenses. In light of the recent case of the former Catalan President, Carles Puigdemont, the abolition has proven to be too hasty and the justificatory force behind the principles of mutual trust and recognition is, with respect hereto, rather limited. The damage caused to these principles by upholding the exemption would be negligible, given the small number of cases-Puigdemont being the first political offender requested under the aegis of the EAW. However, the potential benefits are substantial, given that the exemption provides for a higher level of human rights protection- A nalogous to the values of European Union (EU). Solely relying on the double criminality requirement in order to properly take into account the specificities of the Member States' legal systems essentially positions the judges at the forefront of where mutual trust and constitutional identity collide. Moreover, the exemption prevents states from intervening in other states' internal political conflicts, through the medium of criminal law.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Area of Freedom; Breach of Peace; corruption; Criminal Law; EAW Framework Decision; European Arrest Warrant; extradition law; High Treason; independence referendum; Law of the European Union; mutual recognition; mutual trust; political offense exemption; Security and Justice; sedition; spiritual leader doctrine